Reflections on the 2010 AMR Decade Award: Delivering on the Promise of Entrepreneurship As a Field of Research - Shane, Scott (Academy of Management Review, 2012)
I examine the impact of the 2010 AMR Decade Award article on the entrepreneurship field over the past ten years, identifying aspects of “The Promise of Entrepreneurship As a Field of Research” that have been largely accepted by the field, those that the field has challenged, and those that the field has found to be unclear. I also correct errors made in the earlier work and discuss how the field of entrepreneurship has evolved in response to the publication of the original article.